Semantic memory and depressive symptoms in patients with subjective cognitive decline, mild cognitive impairment, and Alzheimer's disease. (4th April 2017) - Lehrner, J.; Coutinho, G.; Mattos, P.; Moser, D.; Pflüger, M.; Gleiss, A.; Auff, E.; Dal-Bianco, P.; Pusswald, G.; Stögmann, E.
ABSTRACT: Background: Semantic memory may be impaired in clinically recognized states of cognitive impairment. We investigated the relationship between semantic memory and depressive symptoms (DS) in patients with cognitive impairment. Methods: 323 cognitively healthy controls and 848 patients with subjective cognitive decline (SCD), mild cognitive impairment (MCI), and Alzheimer's disease (AD) dementia were included. Semantic knowledge for famous faces, world capitals, and word vocabulary was investigated. Results: Compared to healthy controls, we found a statistically significant difference of semantic knowledge in the MCI groups and the AD group, respectively. Results of the SCD group were mixed. However, two of the three semantic memory measures (world capitals and word vocabulary) showed a significant association with DS. Conclusions: We found a difference in semantic memory performance in MCI and AD as well as an association with DS. Results suggest that the difference in semantic memory is due to a storage loss rather than to a retrieval problem.